Immunisation status of children aged 12 to 23 months: A cross-sectional study at the immunisation clinic of a Government Medical College in West Bengal - Moumita Pal; Avijit Das; Supantha Chatterjee (Journal of Clinical and Scientific Research, 2023)
Background: Immunisation from the very beginning of life not only reduces morbidity and mortality from potentially infectious diseases, it also interrupts disease transmission in the community. Methods: A cross-sectional study was done among children aged 12–23 months, who attended the immunisation clinic of a Medical College Hospital from 6th January to 10th February 2020. They were selected by purposive sampling. A pre-designed, pre-tested, structured questionnaire was applied to collect the relevant data from this group of children. Results: Among the 154 children who participated in the study, 43.5% of them belong to the age group of 16–19 months. 70.8% were found to be fully immunised. However, 28.6% were partially immunised children and only a single participant was found as non-immunised. The immunisation status of the study participants is significantly associated with their religion (P = 0.007) and the educational status of both the parents (P = 0.039, P = 0.04). Conclusions: Overall full immunisation coverage is satisfactory in comparison to National Family Health Survey 4 data (criterion) but not up to the national target. Increased frequency of campaigning and also catch-up immunisation programme should be taken to improve immunisation of those children who were partially immunised or not immunised at all.